Electrospun Naringin-Loaded Fibers for Preventing Scar Formation during Wound Healing - Erika M. Tottoli; Laura Benedetti; Enrica Chiesa; Silvia Pisani; Giovanna Bruni; Ida Genta; Bice Conti; Gabriele Ceccarelli; Rossella Dorati (MDPI AG, 2023)
Hypertrophic scars (HTSs) are aberrant structures that develop where skin is injured complexly and represent the result of a chronic inflammation as a healing response. To date, there is no satisfactory prevention option for HTSs, which is due to the complexity of multiple mechanisms behind the formation of these structures. The present work aimed to propose Biofiber (Biodegradable fiber), an advanced textured electrospun dressing, as a suitable solution for HTS formation in complex wounds. Biofiber has been designed as a 3-day long-term treatment to protect the healing environment and enhance wound care practices. Its textured matrix consists of homogeneous and well-interconnected Poly-L-lactide-co-poly-ε-caprolactone (PLA-PCL) electrospun fibers (size 3.825 ± 1.12 µm) loaded with Naringin (NG, 2.0% w/w), a natural antifibrotic agent. The structural units contribute to achieve an optimal fluid handling capacity demonstrated through a moderate hydrophobic wettability behavior (109.3 ± 2.3°), and a suitable balance between absorbency (389.8 ± 58.16%) and moisture vapor transmission rate (MVTR, 2645 ± 60.43 g/m2 day). The flexibility and conformability of Biofiber to the body surfaces is due to its innovative circular texture, that also allow it to obtain finer mechanical properties after 72 h in contact with Simulated Wound Fluid (SWF), with an elongation of 352.6 ± 36.10%, and a great tenacity (0.25 ± 0.03 Mpa). The ancillary action of NG results in a prolonged anti-fibrotic effect on Normal Human Dermal Fibroblasts (NHDF), through the controlled release of NG for 3 days. The prophylactic action was highlighted at day 3 with the down regulation of the major factors involved in the fibrotic process: Transforming Growth Factor β1 (TGF-β1), Collagen Type 1 alpha 1 chain (COL1A1), and α-smooth muscle actin (α-SMA). No significant anti-fibrotic effect has been demonstrated on Hypertrophic Human Fibroblasts derived from scars (HSF), proving the potential of Biofiber to minimize HTSs in the process of early wound healing as a prophylactic therapy.